Contemporary criminal policy of Germany: example to follow or timely warning? - A. A. Glukhova; D. A. Shpilev (Russian Journal of Economics and Law)
Objective: based on the analysis of publications of German criminologists and sociologists, to identify and describe the main directions of development of modern criminal policy in Germany, including the work of penitentiary system, to determine the influence of new threats (international terrorism) on the regulatory activities of the state and thus on the rights and freedoms of citizens.Methods: general scientific (analysis, systemic-structural approach to the analysis of the study object, comparative legal method) and a specific scientific method - content analysis of scientific publications of German criminologists and sociologists. Results: the author identifies and describes the influence of the so-called new complex threats on the changes in the German criminal policy, namely the emerging trend towards the revival of punitiveness, i.e. tightening of criminal law, as well as the transition of the rule of law state into a preventive one, in which it is necessary to find a balance between freedom and security of citizens.Scientific novelty: the article for the first time examines the potential changes in the modern criminal policy of Germany aimed at building a new security system in the modern "risk society" , the possibility to preserve the fundamental civil liberties; analyzes the danger of dividing criminal law into civil criminal law and special criminal law to combat enemies (for example, terrorists, recidivists, kidnappers); in the context of the national legal policy, alternative (special) forms of deprivation (restriction) of liberty used in Germany are described: "social therapy", assistance to a probationer and establishment of supervision over their behavior, socially useful work, an electronic bracelet.Practical significance: the study results reveal the essential characteristics of possible changes in the modern German criminal policy, which is often criticized for rational humanism and indecision in taking urgent measures. Russia is also actively discussing the issues related to the adequacy of punishment for certain crimes. As a rule, four instruments of criminal policy are identified, the use of which causes the greatest number of disputes both in Russia and in Germany: death penalty, torture, life imprisonment and additional preventive detention. The analysis of the law-making and law-enforcement experience of German colleagues can be very useful, as it will help to avoid unnecessary mistakes, save human, time and financial resources, and prepare our legal system to respond to the most complex challenges of our time.